Implementation of DSN-MUI Fatwa Number 004 of 2003 concerning Productive Zakat for Lazisnu for Business Capital for the People of Muaro Jambi: A Legal Perspective of Maqashid Syariah - Marwiyah; Imron Rosyadi; Rizka (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
This research examines the implementation of Fatwa DSN-MUI Number 004 of 2003 concerning productive zakat by LAZISNU in Muaro Jambi, in supporting community business capital from the perspective of Maqasid Syariah law. This research is field research, data collected through interviews and direct observation, and supported by literature research which includes literature related to productive zakat, sharia economic law, Al-Quran, and Hadith. The results show that LAZISNU applies productive zakat to help mustahiq who meet certain criteria in starting or developing a business, aiming to increase their economic independence. The selection process is done by verification that considers the economic condition, entrepreneurial potential, and mustahiq's business plan. From a Maqasid Syariah perspective, this implementation is in line with the principles of hifz al-mal (maintenance of wealth) and hifz al-nafs (maintenance of soul), where the distributed zakat not only provides short-term benefits, but also strengthens the mustahiq's economy in a sustainable manner. Zakat recipients, through business capital, are expected to be able to create a steady income and fulfill basic needs such as food and shelter. Nonetheless, the main challenge is the low level of public literacy about productive zakat as sustainable business capital, so the awareness to give zakat and its utilization is still low.